First record at molecular level for Rhizoctonia solani causing Rot Root on Aleo vera plants in Iraq - Mazin Badri AL- Ethawi; Huda Hazim AL-Taae (Caspian Journal of Environmental Sciences)
Aloe vera is an important medicinal and cosmetic plant. This study aimed to isolate and diagnose the pathogenic fungi associated with infected Aloe vera in nurseries, Nineveh Province, Northern Iraq in 2020. The results showed the emergence of different pathogenic fungi isolated from the roots, leaves, and stem base (crown area) of Aloe vera. The primary diagnosis based on the morphological characteristics of the fungal colony grown on PDA showed the presence of Rhizoctonia solani with the highest frequency of 82.5%.  R. solani showed different infection symptoms ranging from yellowing and leaf curling, roots in reddish brown colour, and the infection progresses resulted in appearance of reddish necrotic areas on the crown area. The fungal pathogenicity was confirmed using Koch's postulates. Alternaria alternata ranked second with a frequency rate of 55.45% followed by Fusarium solani with 43.75%. The root rot causing R. solani isolate was confirmed by molecular diagnosis using PCR technique. This is considered to be the first study in Iraq for diagnosing fungi on Aloe vera using PCR with pair of specialized primers Forward FITS 5′- TCCGTAGGTGAACCTGCGG-3′ and Reverse RITS 5′- TCCTCCGCTTATTGATATGC-3′. The results showed that the isolate under study belongs to R. solani with a band size of 550 pb, which is the expected size produced by these primers. The results of DNA sequencing of R. solani isolate under study was registered under accession number 1. MW737660. Based on the NCBI information, the isolate showed a similarity in the internal cloning region (ITS) with other isolates by 92-99%.